The marginalisation of voice in the fight against climate change: The case of Lusophone Africa - Hunter, N.B.; North, M.A.; Slotow, R. (Environmental science & policy, 2021)
•English-only searches for African climate change science introduce language-bias.•Non-English literature is poorly represented on Web of Science and Scopus.•Google Scholar incorporates a non-English voice, important for global assessments.•Supporting non-English authors may improve the global uptake of their work.•English-language research translated into local languages may encourage local use. Disregarding research not published in English may pose a risk to finding solutions for urgent global concerns, such as biodiversity loss, or climate change. To assess the extent of this ‘missing voice’, we compared the representation of 22 languages in scientific publications on climate change in Africa, indexed by widely used databases. Between 87 % and 95 % of publications were in English, with a small, but noteworthy, number in languages of the former European colonisers of Africa. We then assessed undergraduate monographs, master’s dissertations, doctoral theses, and peer-reviewed papers derived from the doctoral theses, that are about Lusophone Africa and written in Portuguese, and found this research largely not accessible in English on online databases. If the goal of researchers, practitioners and policy makers is to obtain climate change information on, or present solutions for, individual developing countries, cultures, or localised issues, then searching in English may exclude local, context specific knowledge. This may prevent global assessments from being truly global, or locally down-scalable, by biasing science towards a single world view that marginalises key local stakeholders.